20th Anniversary of the Polish Section of the Audio Engineering Society - Zbigniew KULKA; Wojciech MAKOWSKI; Tadeusz FIDECKI; Maria TAJCHERT (Archives of Acoustics, 2013)
In June 2011, Polish Section of the Audio Engineering Society will celebrate its 20th anniversary. On this occasion, the society officers, ending their second, two-year term, present a short summary of the Section’s activity during the past four years.